The design, experiment, analyse, and reproduce principle for experimentation in virtual reality - Grübel, Jascha (Frontiers in Virtual Reality, 2023)
Conducting experiments in Virtual Reality (VR) requires a complex setup of hardware, software, experiment design and implementation, and data collection that is supported by frameworks that provide pre-determined features for scientists to implement their experiment in VR. These VR frameworks have proliferated exponentially since the start of the millennia and unfortunately, they both only differ slightly from one another and often miss one or more of the key features the researcher requires. Therefore, it has become less clear for researchers which framework to choose for what task and to what benefit. I introduce the Design, Experiment, Analyse, and Reproduce (DEAR) principle to develop a new perspective on VR frameworks through a holistic approach to experimentation (i.e., the process of conducting an experiment). The DEAR principle lays out the core components that future frameworks should entail. Most previous VR frameworks have focused on the Design phase and sometimes the Experiment phase to help researchers create and conduct experiments. However, being able to create an experiment with a framework is not sufficient for wide adoption. Ultimately, I argue, it is important to take reproducibility seriously to overcome the limitations of current frameworks. Once experiments are fully reproducible through automation, the adaptation of new experiments becomes easier. Hopefully, researchers can find ways to converge in the use of frameworks or else frameworks may become a hindrance instead of a help.